SOCIAL ENTREPRENEURSHIP IN ISLAMIC ECONOMIC PERSPECTIVE: A CONCEPTUAL STUDY IN ISLAMIC BOARDING SCHOOLS - Yustanti, Diah Rosna; Dini, Maya; Wijaya, Angka (UIN Raden Mas Said Surakarta, 2025)
This study focuses on developing a conceptual framework of Islamic social entrepreneurship based on maqashid al-shariah and analyzing its relationship with the economic development of pesantren (Islamic boarding schools). Employing an integrative literature review and qualitative content analysis, the research synthesizes theories of social entrepreneurship, maqashid al-shariah principles, and Islamic economic empowerment practices in pesantren. The findings demonstrate that maqashid al-shariah functions as a normative and evaluative framework that guides entrepreneurial activities to achieve equilibrium between spiritual, social, and economic aspects. The values of maslahah, ‘adl, and ta’awun form the ethical foundation for building a fair and sustainable model of social entrepreneurship within pesantren. This study proposes a conceptual model of maqashid-based pesantrenpreneurship that integrates Islamic social values with digital innovation and community cooperation. The study contributes theoretically by extending Islamic social entrepreneurship literature through a maqashid-driven approach and practically by offering strategic guidance for developing pesantrenpreneurship to enhance economic self-sufficiency and community welfare.